PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS BLOG UNTUK MENINGKATKAN PARTISIPASI BELAJAR DAM PEMBELAJARAN IPS DI KELAS VIII J SMP NEGERI 14 BANDUNG - Irfani, Yuda (2013)
This study begins with the issues raised in class VIII J SMP Negeri 14 Bandung related to the lack of participation in learning social studies learning. These issues are findings from observations made at several meetings. Indicator of the problems encountered is the low interest in learning, lack of focus on the learning of students, cenerung passive learners, as well as a lack of initiative in participating in the learning process. Of these problems can be seen that the participation of learners to learning social studies is very low. Review the issues that will be examined relating to the learning process, the researchers chose Classroom Action Research (CAR) with Suharjono research design in 4 cycles. Alternative solutions were selected, namely the use of the use of media -based learning blog. Implementation of the learning activities using blogs as a medium of learning as an alternative to increasing participation in learning social studies can be said to be successful. The increased participation in social studies learning can be seen from the increase in the participation indicators that have an interest in learning social studies learning , able to focus on learning, being able to ask and answer, able to express opinions and be able to do the work on time and deangan collaboration with members of the group. All aspects of this have evolved from the first cycle to the fourth cycle of less quality, reasonably, be good with a percentage of 60.3 %, 67.2 %, 73.5 %, and 71 % in the fourth cycle. In conclusion, the use of Media blog based learning can improve learning in social studies learning participation. Keywords : Media Blog-Based Learning, Participation in social studies learning. Penelitian ini berawal dari permasalahan yang terjadi di kelas VIII J SMP Negeri 14 Bandung terkait kurangnya partisipasi belajar dalam pembelajaran IPS. Permasalahan ini merupakan temuan dari observasi yang dilakukan pada beberapa kali pertemuan. Indikator permasalahan yang dijumpai adalah minat belajar yang rendah, kurangnya fokus peserta didik terhadap pembelajaran, peserta didik cenerung pasif, serta kurangnya inisiatif dalam mengikuti proses belajar. Dari permasalahan tersebut dapat diketahui bahwa partisipasi peserta didik terhadap pembelajaran IPS sangat rendah. Meninjau permasalahan yang akan diteliti berkaitan dengan proses pembelajaran, maka peneliti memilih Penelitian Tindakan Kelas (PTK) dengan desain penelitian Suharjono dalam 4 siklus. Alternatif pemecahan masalah yang dipilih yaitu penggunaan penggunaan media pembelajaran berbasis blog. Pelaksanaan kegiatan belajar menggunakan blog sebagai media pembelajaran sebagai alternatif untuk meningkatkan partisipasi dalam pembelajaran IPS dapat dikatakan berhasil. Adapun peningkatan partisipasi dalam pembelajaran IPS dapat dilihat dari peningkatan indikator partisipasi dalam pembelajaran IPS yaitu mempunyai minat belajar, mampu fokus terhadap pembelajaran, mampu bertanya dan menjawab, mampu mengemukakan pendapat serta mampu mengerjakan tugas deangan tepat waktu dan bekerjasama dengan anggota kelompok. Seluruh aspek ini mengalami perkembangan dari siklus pertama hingga siklus keempat dari kualitas kurang, cukup, menjadi baik dengan persentase 60,3%, 67,2%, 73,5%, serta 71% pada siklus keempat. Kesimpulannya, penggunaan Media pembelajaran berbasis blog dapat meningkatkan partisipasi belajar dalam pembelajaran IPS. Kata Kunci: Media Pembelajaran Berbasis Blog, Partisipasi dalam pembelajaran IPS.